2019
DOI: 10.1111/1556-4029.14167
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification of Kratom (Mitragyna speciosa) and Marijuana (Cannabis sativa) by a Real‐Time Polymerase Chain Reaction High‐Resolution Melt Duplex Assay,

Abstract: Mitragyna speciosa (MS), a plant commonly known as kratom, is a widely used “legal high” opiate alternative for pain relief. DNA extracted from MS and 26 additional plant species was amplified by PCR using primers targeting the strictosidine beta‐D‐glucosidase (SGD) and secologanin synthase 2 (SLS2) genes and detected by high‐resolution melt curves using three intercalating dyes. Amplicon sizes were confirmed using agarose gel electrophoresis. The observed melt temperatures for SGD and SLS2 were 77.08 ± 0.38°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…The PCR HRM results demonstrated that all of the methods were able to extract amplifiable DNA for the plants studied. The melt temperature values obtained in this study with the newly evaluated methods are within or close to the melt temperature ranges determined in previous studies (10,12) with DNA extracted using the Qiagen DNeasy kit. The melt peak shapes were congruent with amplified DNA extracted with the Qiagen kit (10–12).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…The PCR HRM results demonstrated that all of the methods were able to extract amplifiable DNA for the plants studied. The melt temperature values obtained in this study with the newly evaluated methods are within or close to the melt temperature ranges determined in previous studies (10,12) with DNA extracted using the Qiagen DNeasy kit. The melt peak shapes were congruent with amplified DNA extracted with the Qiagen kit (10–12).…”
Section: Resultssupporting
confidence: 85%
“…Table 1 lists their common and scientific names and family. Table 2 lists the PCR primers used in the PCR HRM assays; additional gene and location details can be found in references (10–12,17). Primer stocks of each primer were prepared at 5 μM with the exception of those for morning glory which were prepared at 10 μM in nuclease‐free water.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations